Law Transformation in The Field of International Trade Contract into Indonesian Positive Law - Tan, David (Journal of Law and Policy Transformation, 2018)
Abstract International trade is very influential to economic growth which then influences national welfare and development. This is similar to the idea of a welfare state. Economic rights are also guaranteed by the Indonesian state constitution. On the other hand, international state communities have produced many international legal products that regulate international trade, for example the UNIDROIT Principles of International Commercial Contracts (UPICC), United Nations Convention on Contracts for the International Sale of Goods (CISG) and International Commercial Terms (INCOTERMS). This research was conducted to determine the process of legal transformation into Indonesian positive law. This research is a study from a legal political perspective, because it tries to transform the ius constituendum into ius constitutum. The legal theory used is the Convergence Law Theory to explain the symptoms of legal convergence with the aim of achieving economic efficiency. This research uses juridical normative research. Data sources used are sourced from primary, secondary and tertiary legal data. Data finding is done using library research. Data are then analyzed qualitatively in order to classify the aspects studied. Then, conclusions related to this study were drawn and then described descriptively.     Abstrak Perdagangan internasional sangat berpengaruh terhadap pertumbuhan ekonomi yang kemudian berpengaruh pula terhadap kesejahteraan dan pembangunan nasional. Hal ini mirip dengan gagasan negara kesejahteraan (welfare state). Hak-hak ekonomi juga dijamin oleh konstitusi negara Indonesia. Di satu sisi, komunitas negara internasional telah banyak menghasilkan produk hukum internasional yang mengatur mengenai perdagangan internasional, misalnya UNIDROIT Principles of International Commercial Contracts (UPICC), United Nations Convention on Contracts for the International Sale of Goods (CISG) dan International Commercial Terms (INCOTERMS). Penelitian ini dilakukan untuk mengetahui proses transformasi hukum ke dalam hukum positif Indonesia. Penelitian ini merupakan kajian dari perspektif politik hukum, karena mencoba melakukan transformasi atas ius constituendum menjadi ius constitutum. Teori hukum yang dipergunakan adalah Teori Hukum Konvergensi untuk menjelaskan gejala konvergensi hukum dengan tujuan untuk mencapai efisiensi secara ekonomis. Penelitian ini merupakan penelitian normatif yuridis. Sumber-sumber data yang digunakan bersumber dari data hukum primer, sekunder dan tersier. Penggalian data dilakukan dengan cara studi pustaka (library research). Data dianalisis secara kualitatif dengan tujuan untuk mengklasifikasikan aspek-aspek yang diteliti. Selanjutnya ditarik kesimpulan yang berhubungan dengan penelitian ini dan kemudian diuraikan secara deskriptif.